Human‐enteric‐coronaviruslike particles (CVLP) with different epidemiological characteristics - Sitbon, Marc (J Med Virol, 2005)
One hundred fifty‐six diarrheic and 115 control stools collected throughout a year from nonhospitalized children were examined by electron microscopy in Haut‐Ogooué, Gabon; 65.2% of the controls and 38.5% of the diarrheics were found to contain coronaviruslike particles (CVLP). In both diarrheic and control groups the CVLP prevalences showed a seasonal variation whereas significant variation of prevalence with age was observed only in the controls. Thus, the CVLP in controls were significantly more abundant in children over 2 years old (76% vs 48%, P < .01) and more frequently observed during the months of rainy seasons (75% vs 54%, P < .02). On the other hand, the higher prevalence of CVLP in diarrheics over 2 years old was not significant (48% vs 36%, P = .20), whereas a significantly lower prevalence of CVLP during the months of rainy seasons was observed in this group (27% vs 50%, P < .01). Studies of the climatological factors in this equatorial climate showed a parallel cyclical variation of parameters representing rainfall, temperature, as well as relative humidity. We were not able to distinguish which of these factors was influencing more directly the prevalence of CVLP.